Wangkiny Yirra “Speaking Up” project: First Nations women and children with disability and their experiences of family and domestic violence - Jones, Jocelyn; Roarty, Lynn; Gilroy, John; Brook, Juliet; Wilson, Mandy; Garlett, Cathy; McGlade, Hannah; Williams, Robyn; Leonard, Helen (Royal Commission into Violence, Abuse, Neglect and Exploitation of People with Disability, 2023)
First Nations women and children with disability are at greater risk of family and domestic violence (FDV) and its consequences than their non-Indigenous peers. A recent report (Ringland et al., 2022) found that First Nations women with disability had the highest rates of victimisation of any group, with 34.4% recorded as being victims of crime. Despite this, the voices of First Nations people are largely missing from disability research in Australia (Dew et al., 2019).